Student-Led Digital Ecosystems in Humanities: A Mixed-Methods E-Learning Study - Prasanth Arokia Samy D.; Alagu Revathi L; Cohiran J (International Journal Labs, 2026)
The rapid advancement of digital technology has transformed higher education by creating new possibilities for student-centred and participatory learning environments. However, humanities education continues to face challenges related to student engagement, digital adaptation, and the relevance of traditional learning approaches in the digital era. This study aims to examine how a student-led digital ecosystem functions as a technology-enhanced learning environment and how participation in digital platforms contributes to students’ learning outcomes. This research employed a convergent mixed-methods design involving both quantitative and qualitative data collection. The participants consisted of 50 undergraduate and postgraduate students selected through purposive sampling from the PG and Research Department of English at St. Joseph’s College (Autonomous), Tiruchirappalli, India. Data were collected through structured questionnaires, open-ended feedback, and platform engagement records, which were analysed using descriptive statistics and thematic analysis. The findings indicate that student-led digital platforms, including digital publishing, podcasts, mobile applications, and social media, effectively support learning through content creation, collaboration, and active participation. Students reported improvements in communication skills, digital literacy, creativity, confidence, and teamwork. The study concludes that student-driven digital ecosystems can serve as sustainable and inclusive models of technology-enhanced learning, particularly in resource-constrained higher education contexts. This research contributes to digital pedagogy by demonstrating that meaningful digital transformation depends not only on technological infrastructure but also on student agency, collaborative practices, and contextually relevant learning design.